The long term impact of cataract surgery on quality of life, activities and poverty: results from a six year longitudinal study in Bangladesh and the Philippines. - Lisa Danquah; Hannah Kuper; Cristina Eusebio; Mamunur Akm Rashid; Liza Bowen; Allen Foster; Sarah Polack (PLoS ONE, 2014)
BACKGROUND: Cataract surgery has been shown to improve quality of life and household economy in the short term. However, it is unclear whether these benefits are sustained over time. This study aims to assess the six year impact of cataract surgery on health related quality of life (HRQoL), daily activities and economic poverty in Bangladesh and The Philippines. METHODS AND FINDINGS: This was a longitudinal study. At baseline people aged ≥50 years with visual impairment due to cataract ('cases') and age-, sex-matched controls without visual impairment were interviewed about vision specific and generic HRQoL, daily activities and economic indicators (household per capita expenditure, assets and self-rated wealth). Cases were offered free or subsidised cataract surgery. Cases and controls were re-interviewed approximately one and six years later. At baseline across the two countries there were 455 cases and 443 controls. Fifty percent of cases attended for surgery. Response rates at six years were 47% for operated cases and 53% for controls. At baseline cases had poorer health and vision related QoL, were less likely to undertake productive activities, more likely to receive assistance with activities and were poorer compared to controls (p<0.05). One year after surgery there were significant increases in HRQoL, participation and time spent in productive activities and per capita expenditure and reduction in assistance with activities so that the operated cases were similar to controls. These increases were still evident after six years with the exception that time spent on productive activities decreased among both cases and controls. CONCLUSION: Cataract causing visual loss is associated with reduced HRQoL and economic poverty among older adults in low-income countries. Cataract surgery improves the HRQoL of the individual and economy of the household. The findings of this study suggest these benefits are sustained in the long term.